Electrocardiography-gated CT for acute aortic syndrome: quantifying the potential impact of subspecialty national recommendations on emergency general radiology reporting. Issue 1 (January 2022) - Hamilton, M.C.K.; Harries, I.; Lopez-Bernal, T.; Karteszi, H.; Redfern, E.; Lyen, S.; Manghat, N.E.
Abstract : AIM: To evaluate the detection of acute aortic syndrome (AAS) and the prevalence of alternative diagnoses that may explain the presentation or require follow-up. MATERIALS AND METHODS: This was a retrospective, blinded re-evaluation of consecutive electrocardiography (ECG)-gated computed tomography (CT) aortic studies by a cardiovascular radiologist performed between September 2019 and May 2020 in a tertiary-referral cardiothoracic centre. RESULTS: There were 118 identified examinations, six examinations were excluded leaving 112 (mean age = 61 ± 17; 56% male). Three cases of AAS were present (prevalence 2.7%); only one was reported on initial review. There were no false-positive diagnoses of AAS. The heart was mentioned in 79 (70.5%) reports and 73 (65.2%) of reviews revealed a total of 114 new observations; 111 (97.4%) of these were cardiovascular with 44/112 (39.3%) patients potentially having a significant previously unsuspected cardiovascular diagnosis. CONCLUSION: The implementation of national clinical guidance to increase testing and improve image quality led to a series of challenges. The real value of ECG-gated CT may lie in detecting other diseases that mimic AAS. With the additional workload, increased subspecialty expertise is required but there needs to be a willingness to learn with an adequate support infrastructure. Highlights: Concern for AAS leads to more CT, low disease prevalence and alternative diagnoses. 62% of reports had omissions of which 97.4% were cardiovascular. 39.3% of reports had unreported possible explanatory cardiovascular findings.